VD_FINDINFO Décision / 2013 / 1049 vom 19. Dezember 2013 - VD Tribunal cantonal (2013)
DÉTENTION PRÉVENTIVE, SOUPÇON, RISQUE DE FUITE, RISQUE DE RÉCIDIVE | 221 al. 1 let. a CPP (CH), 221 al. 1 let. c CPP (CH), 228 CPP (CH)